Virtual antenna array for wireless sensor network localization - Rubis, Christopher Allen O. (2010)
A wireless sensor network (WSN) is a low power, low data rate communication system with ease of deployment for monitoring and detection application specifically on creep movement for impending landslide event. However, localization application requires movement detection and direction of the target node. Several studies on localization technique are being studied from GPS up to transducer (i.e. infrared and acoustics) integration to WSN. However, localization techniques are limited to power consumption, complexity of the algorithm, localization range, accuracy, reliability and cost. Radio frequency (RF) localization technique using phase characteristic of the RF signal is a reliable parameter for relative localization estimation technique. The study will establish the virtual antenna array (VAA) technique used in WSN technology for direction estimation and reliable movement detection. The VAA technique is a uniformly spaced array node WSN in a linear configuration that detects movement using RF signals emitted by target node. The phase shift of the RF signal with respect to antenna array node wave font was calibrated and constructs the covariance matrix (Rxx) for post processing using Multiple Signal Classification (MUSIC) algorithm. A reliable and repeatability phase acquisition was conducted in this paper.